Prescribed performance finite‐time control of wind energy conversion systems with input constraint and system uncertainty. (9th December 2021) - Jing, Fengmei; Liu, Weijie; Sun, Hanbing; Yu, Fengwei; Wang, Kai
Abstract: In this paper, the maximum wind power tracking control problem for the wind energy conversion system is considered and two effective algorithms are presented to solve it. The main contributions are as follows: (a) An improved prescribed performance control algorithm is proposed. By using a new performance function and a new error transformation scheme, the proposed controller can solve overshoot problems and guarantee tracking error to reach its stability region within finite time. (b) The nonsingular terminal sliding mode prescribed performance control algorithm is proposed. In order to solves finite time convergence and avoid the generation of singularity for wind energy conversion system, a finite‐time stable controller is designed by combining the nonsingular terminal sliding mode technique and a finite‐time prescribed performance function. Furthermore, a finite‐time observer is used to estimate the system uncertainties. An auxiliary system is introduced to solve the problem of control input saturation. The stability of the system is proved by using Lyapunov theory. The feasibility of the proposed methods is verified by the simulation results. The research conducted in this paper will make great significance for the study of maximum wind power tracking control problem. Abstract : In this paper, the maximum wind power tracking control problem for the wind energy conversion system with input constraint and system uncertainty is considered and a new algorithm is presented to solve it.